PENGARUH DISIPLIN KERJA, PEMBERIAN REWARD DAN PENGETAHUAN MANAJEMEN TERHADAP KINERJA KARYAWAN PADA PT. PESONA INTI RASA - Salsabillah, Fauziah Mei; Tambunan, Debora (Jurnal Mahkota Bisnis (Makbis), 2025)
The purpose of this study is to determine how influential work discipline, reward provision and management knowledge are on employee performance at PT. Pesona Inti Rasa. The method used in this study is quantitative. The population in the study is 80 employees sourced from the personal management of PT. Pesona Inti Rasa, while the determination technique by researchers using saturated samples. The data sources in this study are from primary data and secondary data, while the data analysis method used in this study is multiple linear regression analysis. From the results of this study it can be seen that the questionnaire statement items are declared valid because the r count value> r table while the results of the reliability test of the research results obtained that all questionnaire statement items are declared reliable because the Cronbach Alpha value is above the reliable limit value. Partially, the influence of the work discipline variable (X1) has a positive and significant effect on employee performance (Y) where the work discipline variable has a t count value from the t table. Partially (one by one) the influence of the reward variable (X2) has a positive and significant effect on employee performance (Y) where the reward variable has a t count value from the t table. Partially (one by one) it is found that the influence of the management knowledge variable (X3) does not affect employee performance (Y) where the management knowledge variable (X3) has a calculated t value from the t table. and Overall (simultaneously) it is found that the influence of the work discipline variable (X1) and the provision of rewards (X2) has a positive and significant effect on employee performance (Y) because the calculated F value for the employee performance variable (X1) and the provision of rewards (X2) is > F.table, while the management knowledge variable (X3) does not affect employee performance (Y) because the calculated F value for the management knowledge variable (X3) < F.table. The results of the determination obtained by work discipline (X1) and the provision of rewards (X2) can show a strong relationship to employee performance.